Effects of led red and blue spectra irradiance levels and nutrient solution ec on the growth, yield, and phenolic content of lemon basil (Ocimum citriodurum vis.) - Daud, Zurafni Mat; Ismail, Mohd Firdaus; Hakiman, Mansor (MDPI, 2023)
This research was conducted to study the effects of LED red and blue spectra irradiance levels and nutrient solution (electrical conductivity) and their interaction on the plant growth, yield, and phytochemical contents of lemon basil (Ocimum citriodorum Vis.) in a controlled environment. The controlled environment was equipped with red and blue spectra at a 4:1 ratio with irradiance levels of 80 and 160 µmol m−2 s−1 and irrigated with four different nutrient solution ECs at 1.0, 1.8, 2.6, and 3.4 mS cm−1, cultivated on a vertical structure. The temperature and relative humidity of the controlled environment and the pH of the nutrient solution were maintained at 26 and 18 °C day and night, 65 ± 5%, and pH 6, respectively. It was observed that plant height, canopy diameter, and the number of leaves of lemon basil had significantly increased under the irradiance levels of 160 µmol m−2 s−1 in combination with a nutrient solution EC of 2.6 mS cm−1. In addition, there was an interaction observed between the LED irradiance levels and the nutrient solution EC on the fresh weight of the stem and the dry weight of all the plant parts (leaves, stem, and roots). Lemon basil cultivated at 160 µmol m−2 s−1 and irrigated with 2.6 mS cm−1 was significantly higher in fresh stem weight and dry leaf, stem, and root weight at 17.36, 1.79, 1.82, and 0.22 g, respectively. The ascorbic acid of lemon basil was significantly higher under a treatment of 160 µmol m−2 s−1 irradiance level and an EC of 2.6 mS cm−1, and no interaction was observed. At the same time, there was an interaction observed between the LED irradiance level and the nutrient solution EC on the total phenolic content (TPC), total flavonoid content (TFC), and caftaric acid concentration of lemon basil. Lemon basil cultivated at 160 µmol m−2 s−1 and irrigated with 2.6 mS cm−1 was significantly higher in TPC, TFC, and caftaric acid concentration, with 1440.62 mg gallic acid equivalent to 100 g−1 DW, 1148.79 mg quercetin equivalent to 100 g−1 DW, and 2812.50 mg 100 g−1 DW, respectively. This result indicates that the irradiance levels of red and blue LED spectra at 160 µmol m−2 s−1 and irrigated with a nutrient solution EC of 2.6 mS cm−1 enhances the growth, yield production, and phenolic content of lemon basil in a controlled environment facility.